SPX Express: Pengaruh Layanan Pengiriman terhadap Retensi via Kepuasan pada E-commerce Shopee Indonesia - Hartono, Hartono; Padmalia, Metta; Tambunan, Damelina Basauli (Universitas Batanghari Jambi, 2025)
This study aims to analyze the effect of SPX Express delivery services on customer retention on the Shopee Indonesia platform by placing customer satisfaction as a mediating variable. This study is based on Expectancy Disconfirmation Theory (EDT) and uses a quantitative approach through an online survey of 173 active Shopee users selected using a purposive sampling technique. Data were analyzed using Structural Equation Modeling (SEM) to examine the relationship between variables. The results of this study reveal that SPX Express delivery services have a significant influence on Shopee Indonesia customer satisfaction, where customer satisfaction is proven to be a major factor driving retention. In addition, delivery services also influence customer retention both directly and indirectly through the mediation of customer satisfaction. Thus, the quality of delivery services plays a strategic role not only in increasing satisfaction but also in strengthening customer loyalty on the Shopee Indonesia e-commerce platform.